An investigation of learning strategies & personality traits among proficient & less proficient ESL learners - Arthur, Christine Shobana; Ng, Lee Luan (Journal of Modern Languages, 2009)
The purpose of this study is to provide an insight in determining the link between personality, language learning strategies and proficiency. Personality traits make a difference in affecting how people learn and what they learn (McCaulley & Natter; Myres & Myres, as cited in Moody, R., 1988). In view of this, this study explores the various combinations of language learning strategies that are utilized by proficient and less proficient Malaysian ESL learners according to their personailty traits. In order to ascertain the personality traits and learning strategies employed, the Keirscy Four Types Sorter (KTS) is used to collect data on the personality type of the ESL learners, while the Strategy Inventory for Language Learning (SILL) is used to indicate the subject’s preferred language learning strategies. This study attempts to investigate the personality factors that influence proficient and less proficient ESL learners in choosing their language learning strategies. The findings reveal that personality is not significantly related to language learning strategies, yet choices of language learning strategies are related with proficiency to a certain extent. The outcome of the present study would be useful to assist language instructors in helping less proficIent ESL learners in undergoing a more effective and successful second language leaming experience and enlighten proficient ESL learners about their preference in language learning strategies.